Sistem Pakar Deteksi Penyakit Diabetes Mellitus (DM) menggunakan Metode Forward chaining dan Certainty factor Berbasis Android - Utami, Yulianti Pratiwi; Triayudi, Agung; Esthi Handayani, Endah Tri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Excess sugar consumption will affect the body's resistance with predicted dangers such as diabetes. Diabetes is a disease that is a quite a dangerous cause of the failure of the pancreas to produce the hormone insulin. Information regarding the achievement of blood sugar targets that must be understood by some people is around 80-130mg / dL because of the lack of effectiveness in consulting directly with experts, the aim of this study is to make a problem solving using an expert system by applying the forward chaining method and certainly a factor. Also implemented on the Android operating system so that the use of every detail of this application can be accelerated by the hand with a smartphone. As a result, every user of this application can ask questions that can diagnose Diabetes Mellitus.Keywords:Expert System, Forward chaining, Diabetes Mellitus Detection, Certainty factor, Android.